Effectiveness of cervical cancer therapy using neoadjuvant chemotherapy in combination with radical surgery: a meta-analysis - Fu, Yijie; Zhu, Tianmin; Li, Hui (Translational Cancer Research, 2017)
Background: Cervical cancer is the fourth of most common cancers, and also the fourth cause of women death in the world. Neoadjuvant chemotherapy (NACT) combined with conventional radical surgery (RS) has been proposed to be able to eradicate the micro metastasis for advanced cervical tumors so that improve the survival of cancer patients. However, the effectiveness of combined treatment of both NACT and RS is still a debate. Results from different studies are usually inconsistent, even contradictory. Methods: To evaluate the advantage of the combination of NACT and RS over RS alone for cervical cancer, we performed a meta-analysis, which involved eight case-control studies. Two-year and 5-year disease-free survival (DFS) and overall survival (OS) were compared with stratification analysis in each group with regard to the surgical-pathologic high risk factors including lymph node metastasis, positive surgical margin, parametric infiltration, lymphovascular invasion, cervical stromal depth and positive pelvic nodes. Results: Our study showed that cervical cancer patients with additive NACT treatment may have no additional benefit for the long-term OS and DFS than RS alone group [2-year OS: odds ratios (ORs) =1.008; 95% confidence intervals (CIs), 0.832–1.220; P=0.937; 5-year OS: OR =1.054; 95% CI, 0.860–1.292; P=0.913; 2-year DFS: OR =1.015; 95% CI, 0.853–1.207; P=0.870; 5-year DFS: OR =1.001; 95% CI, 0.816–1.228; P=0.992]. Further subgroup meta-analysis of adjuvant therapy and stratification adjustment with six surgical–pathologic risk factors also drew the same conclusion. Conclusions: These results suggested that NACT might not be effective enough to elongate patients survival as been reported by some studies, further confirmation needs to be done by more profound analyses.